Efeito do dibenzotiofeno - DBT (derivado do petróleo) no crescimento e na morfologia de rhizopus arrhizus UCP 402 - Inácio, Renata Gonçalves dos Santos (2010)
The present work had as objective investigate the effect of dibenzotiofene - DBT (derived from oil) in the growth and morphology of Rhizopus arrhizus UCP 402. Had the increase of the use of the fossil fuels used for some industrialized countries, a serious environment problem aggravates due to quality of the reserves of the oil, in view of the amount of sulphur, and consequently, greater toxicity for the environment. In turn, the dibenzothiofene (DBT) is a composition heterociclic organossulfurated in the oil diesel, being considered a great fuel that cause ambient problems. The use of the DBT for R. arrhizus UCP 402 was evaluated from different concentrations of this composition, having observed itself the effect in kinetic of growth and the morphology, in the production of quitina and quitosana, as well as in the formation of toxic methabolits. The gotten results had indicated that R. arrhizus presents ability to grow in the different concentrations of the composition, however only, in co-metabolism, that is, in the glucose presence. A variation in the total protein text, quitina and quitosana for the action of the DBT was observed. The óptic microscopy evidenced variations in the morphology of R. arrhizus, also causing alterations in the ramification of hifas on standard. The products of the metabolism of the DBT had indicated that degradation of the composition for R. arrhizus occurred, whose methabolits had presented one accented inhibition of the germination of Cabbage of the 4 stations (oleracea Brassica to var. capitata). The carried through studies had demonstrated a great biotechnological potential of R. arrhizus in the process of degradation of DBT, being able to be used in the future in biorremediation processes.